The Marvelous and Fantastic Narration in the Novel "Athar Al-Maho" - Ali, Dr. Noufa Hussein (Thi Qar Arts Journal, 2025)
This study explores the fantastic and strange narrative elements in the novel Ithar al-Mahw by the novelist Maytham Tahir. The novel is considered one of the contemporary literary works that captures artistic and creative dimensions through innovative expressive techniques. These techniques address reality through the unreal, disrupting the familiar and destabilizing it. This is manifested through transformations, horror, the irrational, hallucinations, and dreams, in addition to the emergence of mysterious and unstable characters and settings. These elements collectively contribute to a narrative experience that balances between astonishing the reader and prompting reflection on the nature of reality.The use of the fantastic and the strange in narrative fiction has multiple functions that influence characters and objects within the narrative space. Therefore, Ithar al-Mahw by Maytham Hashim Tahir serves as an applied model, being one of the contemporary novels rich in fantastic and strange dimensions.